Perceptions on voluntary adoption and certification of food safety management system HACCP: a case study of A&B staff in a five-star hotel in Brazil (Research, Society and Development, 2021)
This study uses the in-depth case study method to evaluate the perceptions of managers and handlers of the Food and Beverage (A&B) sector of a five-star hotel that has as a differential the certification by a Food Safety Management System (FSMS), based on Hazard Analysis and Critical Control Points (HACCP), for some of the products of its breakfast buffet. The data were collected through semi-structured interviews with 6 managers from the A&B sector and a survey with their teams of food handlers (N = 105), being later analyzed by Content Analysis, supported by Atlas.tiÔ v.5.5 and descriptive statistics supported by SPSSÔ v. 14.0, respectively. The questionnaire used was previously tested, through consultation with experts and pre-test with a group of 20 food handlers from another hotel in the same hotel chain and with similar characteristics. The results obtained show considerable contrast in the socioeconomic classes and education of the employees of both groups, which may influence their overall perceptions of food safety. And, although both groups agree that an FSMS based on a voluntary and certified HACCP system can represent a competitive advantage for the hotel, most food handlers do not seem to perceive certified products differently in practice. Finally, the study points out the need to better communicate food safety certification in hotels in order to make it tangible, transferring added value to the business.